2017
DOI: 10.3928/19382359-20170111-01
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Nicotine Delivery Systems Among Adolescents: Status of the Evidence and Public Health Recommendations

Abstract: Although the prevalence of tobacco smoking has been declining in recent years, the use of electronic nicotine delivery systems (ENDS) such as of electronic cigarettes, vaporizers, and hookahs has been steadily rising, especially among adolescents. ENDS are not only advertised to children, but their sale via the Internet has made them easily accessible to youth. In general, children perceive ENDS as safe, or at least safer than smoking traditional combustible tobacco products; however, exposure to nicotine may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Several surveys reported that the main reasons for using e-cigarettes are that it is fun, enjoyable and cool 41-43 . These findings are consistent with survey results in Hong Kong 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Several surveys reported that the main reasons for using e-cigarettes are that it is fun, enjoyable and cool 41-43 . These findings are consistent with survey results in Hong Kong 16 .…”
Section: Discussionmentioning
confidence: 99%
“…EL may also cause headaches or diarrhea (Glasser et al , 2017). The long-term health effects of EC use are not clear; however, several studies have suggested that ECs might contribute to respiratory disease (Grana et al , 2014; Palamidas et al , 2014), high blood pressure (Loysamut, 2018) and disturbed brain development among adolescents (Office of the Surgeon Gen, 2016; Kamat and Van Dyke, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Although experts largely agree that e-cigarettes are less harmful than combustible tobacco products (Bhatnagar et al, 2014;Chen, Bullen, & Dirks, 2017), these products still pose harms, especially for youth. These include the potential for respiratory harm (Grana, Benowitz, & Glantz, 2014;Palamidas, 2013), increased blood pressure (Office of the Surgeon General, 2016), and harms to brain development (Kamat & Van Dyke, 2017; Office of the Surgeon General, 2016). A recent meta-analysis demonstrated that adolescents who use e-cigarettes are at least three times more likely to initiate combustible cigarette use (Soneji et al, 2017).…”
Section: Introductionmentioning
confidence: 99%